Reviews - Marciniak, Katarzyna; Rozzi, Stefano; Kontonasios, Panagiotes; Mandrino, Alessandro (Ciceroniana On Line, 2021)
Christoph PIEPER, Bram VAN DER VELDEN (eds.), Reading Cicero’s Final Years: Receptions of the Post-Caesarian Works up to the Sixteenth Century. With Two Epilogues (K. MARCINIAK) Tommaso RICCHIERI, Prima della Sicilia. Cicerone, Verrine 2,1. (De praetura urbana), 1-102, Introduzione, testo critico, traduzione e commento (S. ROZZI) Juan Carlos IGLESIAS-ZOIDO (ed.), Conciones ex historicis excerptae. Nuevos estudios sobre las antologías de discursos historiográficos (P. KONTONASIOS) Lisa MAURICE (ed.), Our Mythical Education. The Reception of Classical Myth Worldwide in Formal Education, 1900-2020 (A. MANDRINO)